Antimicrobial prescribing quality in Australian emergency departments: an analysis of the Hospital NAPS data set - Lenna Zosky-Shiller; Karin Thursky; Sarah Park; Rodney James; Lisa Hall; Caroline Chen; Courtney Ierano (Antimicrobial Stewardship & Healthcare Epidemiology)
Abstract